Implementing a stabilizing intervention for traumatized refugees in temporary accommodations in South-West Germany: a randomized controlled pilot trial - Rzepka-Marot, Irja; Zehetmair, Catharina; Nagy, Ede; Friederich, Hans-Christoph; Nikendei, Christoph (Frontiers in psychiatry, 2024)
The prevalence of trauma-related disorders, such as post-traumatic stress disorder (PTSD), as well as depressive or anxiety disorders, are significantly increased in refugees compared to the general population. This is due to the high risk of burdening and potentially traumatic experiences before, during and after their flight. However, the treatment options for these mental illnesses are significantly limited due to the legal uncertainties surrounding the asylum procedure as well as language and cultural barriers. In this study, a randomized controlled pilot trial was conducted to assess the effectiveness of self-applied audio-based mindfulness and guided imagery techniques for refugees with symptoms of post-traumatic stress disorder living in temporary accommodations. The symptom burden of PTSD, depression, and anxiety symptoms, as well as perceived stress and emotional state was assessed using the PC-PTSD-5, PHQ-4, Self-Assessment Manikin, and Stress Thermometer. N=32 refugees were included in the intervention study, n=24 participants completed the study. The audio-based mindfulness and guided imagery techniques were presented to n =17 refugees in the intervention group between T1 and T2 over 4 weeks; n=15 refugees from the waiting list control group received the audio-files 6 weeks after follow-up. Efficacy was evaluated using a mixed analysis of variance. There were no significant changes in the symptoms of post-traumatic stress disorder, depression and anxiety disorder. Moreover, no changes were observed in the level of perceived stress or emotional state. Only few participants used the exercises in self-administered application during the study period. This was mainly due to the stressors of the post-migratory phase, such as job search or worries about residence status. Due to the self-administered nature of the intervention, common factors, such as therapeutic alliance or expectations regarding the intervention’s effectiveness, had minimal influence and did not contribute to the sustained use of the exercises. Additionally, regarding the life circumstances of refugees in temporary shelters, the intervention intensity may not have been sufficient to have a significant impact on the examined symptom burden. Small sample size and limited use of the exercises limit the reliability of the results. Clinical trial registration https://drks.de/search/de/trial/DRKS00022862 Deutsches Register Klinischer Studien identifier, DRKS00022862.